2023
DOI: 10.1530/ec-23-0013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D level regulates serum lipids discrepantly in adults with and without dyslipidemia

Abstract: Vitamin D deficiency is associated with hyperlipidemia, but it remains unclear whether vitamin D supplementation reduces serum lipid levels. The aims of this study were to investigate the associations between increased serum 25-hydroxyvitamin D (25(OH)D) concentrations and lipid levels, and identify the characteristics of people with or without lipid reduction associated with increased 25(OH)D levels. The medical records of 118 individuals (53 men; mean age, 54.4 ± 10.6 years) whose serum 25(OH)D levels increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…HDL-C was lower and TGs were higher in the hypovitaminosis D group [ 21 ]. Similar positive associations have been observed in numerous other studies conducted across various populations [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. A recent cross-sectional study confirmed that the percentage of individuals with dyslipidemia and dysglycemia was higher in subjects with low levels of vitamin D [ 33 ].…”
Section: Resultssupporting
confidence: 89%
“…HDL-C was lower and TGs were higher in the hypovitaminosis D group [ 21 ]. Similar positive associations have been observed in numerous other studies conducted across various populations [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. A recent cross-sectional study confirmed that the percentage of individuals with dyslipidemia and dysglycemia was higher in subjects with low levels of vitamin D [ 33 ].…”
Section: Resultssupporting
confidence: 89%
“…Regarding vitamin D intake, the GLUT1-DS group received an average supplementation of 660 IU/day to complete the recommended requirements according to age and gender. Although there are no studies that evaluate the effect of supplementation in subjects similar to those in our study, evidence suggests that deficiency of this vitamin may be related to a higher risk of dyslipidemia, and correcting it could be beneficial for individual health, especially among adults (22,23).…”
Section: Discussionmentioning
confidence: 74%
“…It was reported that vitamin D deficiency is associated with hyperlipidemia, and elevated human serum 25OHD levels were associated with decreased human serum TC and TG levels, especially in patients with hyperlipidemia who were vitamin D deficiency. 14 Therefore, increasing the concentration of circulating 25OHD may be used as an adjunct therapy for hyperlipidemia. 14 It has a certain reference value for clinical diagnosis and treatment.…”
Section: Resultsmentioning
confidence: 99%
“…14 Therefore, increasing the concentration of circulating 25OHD may be used as an adjunct therapy for hyperlipidemia. 14 It has a certain reference value for clinical diagnosis and treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation